2014
DOI: 10.1007/s13205-014-0244-7
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation and assessment of genetic fidelity of Dendrocalamus strictus (Roxb.) nees using RAPD and ISSR markers

Abstract: Dendrocalamus strictus popularly known as ‘Male bamboo’ is a multipurpose bamboo which is extensively utilized in pharmaceutical, paper, agricultural and other industrial implements. In this study, in vitro regeneration of D. strictus through nodal culture has been attempted. Murashige and Skoog’s medium supplemented with 4 mg/l BAP was found to be most effective in shoot regeneration with 3.68 ± 0.37 shoots per explant. The effect of Kn was found to be moderate. These hormones also had considerable effect on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 27 publications
3
34
0
1
Order By: Relevance
“…2. Similar results were reported in micro-propagated shoots of Curcuma longa (Salvi et al 2001), sugarcane (Khan et al 2009), Gerbera jasmesonii (Bhatia et al 2011), Momordica dioica (Rai et al 2012), Terminallia bellerica (Dangi et al 2014), and Dendrocalamus strictus (Goyal et al 2015). Zucchi et al (Zucchi et al 2002) reported that polymorphism occurred in sugarcane shoots regenerated from meristem cultures because of the number of subcultures and RAPD analysis was used for detection of polymorphism.…”
Section: Resultssupporting
confidence: 74%
“…2. Similar results were reported in micro-propagated shoots of Curcuma longa (Salvi et al 2001), sugarcane (Khan et al 2009), Gerbera jasmesonii (Bhatia et al 2011), Momordica dioica (Rai et al 2012), Terminallia bellerica (Dangi et al 2014), and Dendrocalamus strictus (Goyal et al 2015). Zucchi et al (Zucchi et al 2002) reported that polymorphism occurred in sugarcane shoots regenerated from meristem cultures because of the number of subcultures and RAPD analysis was used for detection of polymorphism.…”
Section: Resultssupporting
confidence: 74%
“…RAPD and ISSR has been successfully applied to determine genetic fidelity/stability in several micropropagated plant systems viz. sugarcane (Suprasanna et al 2006; Devarumath et al 2007; Lal et al 2008), Chlorophytum borivilianum (Rizvi et al 2012), Terminalia beelerica (Dangi et al 2014), Aloe barbandesis (Sahoo and Rout 2014), Swertia lawii (Kshirsagar et al 2015), Dendrocalamus strictus (Goyal et al 2015), Dendrocalamus hamiltonii (Singh et al 2013) etc. These markers have been successfully applied for the detection of polymorphisms that are either induced or incorporated during in vitro regeneration of several plant species (Asthana et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Callus induction was initiated in media containing different concentrations of 6-benzyl amino purine (BAP) as cytokinin and 1-napthaleneacetic acid (NAA) or 2,4 dichloro-phenoxy acetic acid (2,4-D) as auxins. Subculturing was done at a regular interval of 2 weeks in the same media having the same hormonal composition [11]. BAP, NAA and 2,4-D at the rates of 1, 2, 3 or 4 mg•L −1 were supplied to observe various stages of in vitro callus induction.…”
Section: Callus Induction and Somatic Embryo Productionmentioning
confidence: 99%